THE EFFECT OF MANAGERIAL OWNERSHIP, CASH RATIO, DEBT-TO-EQUITY RATIO, AND SALES GROWTH ON DIVIDEND POLICY IN CONSUMER GOODS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2020 PERIOD - Fauzia Listianto; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
The purpose of this research is to analyze the influence of Managerial Ownership, Cash Ratio, Debt to Equity Ratio, and Growth Opportunity on dividend policy in the consumer goods industry listed on the 2015 IDX. -2020. The population in this research is the industry in the Consumer Goods Sector during the 2015-2020 period. With a purposive sampling method from 15 industries. . Documentation is used as a data collection method. The study data were analyzed using a panel data regression approach with a significance level of 0.05 using STATA 13 software. This analysis shows that CR has a positive and significant effect on dividend policy, whereas KM, DER and GO have no significant effect on dividend policy.